Sending en Pentateugkritiek - Le Roux, J. H. (Verbum et ecclesia, 1990)
Mission and criticism of the Pentateuch Criticism of the Pentateuch was looked at with scepticism by many during the nineteenth century in England. John William Colenso (1814—1883) was bishop of Natal and was of different opinion. His thorough investigation of the Pentateuch was sparked off by a question about the historical reliability of the Flood narrative. Colenso’s results about the nature and growth of the Pentateuch were diametrically opposed to the existing views. He was accused of heresy and viewed as a destroyer of the Bible. Colenso defended himself but it was of no avail.